القيم الفلسفية في كتاب الأدب الصغير والكبير لابن المقفع: Philosophical Values in Ibn Al-Muqaffa’s Kitab Al-Adab Al-Shagir and Al-Adab Al-Kabir - Kholil, Ahmad; Ainin, Moh; Faisol, M; Hasanah, Ummi; Wirmansyah, Aulia Fadhila (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2025)
This research aims to identify and to analyze the philosophical values contained in Ibn al-Muqaffa’s Kitab al-Adab al-Shagir and al-Adab al-Kabir. The main focus of this research is to explore how moral philosophy or ethical concepts are reflected in these two literary works and their relation to divine values, cosmology and humanism. This research is a literature study using a qualitative-descriptive analysis method. The primary data sources are texts from these two works as primary sources, as well as books and other references discussing philosophy and literature as secondary sources. The qualitative-descriptive method is used to systematically and deeply elaborate the data. The approach employed is content analysis with a philosophical perspective. This analysis is based on two ways of understanding: first, understanding the content within literary works and second, understanding communication as an interaction between the works and the readers. The findings of this research indicate that the philosophical values in Kitab al-Adab al-Shagir and al-Adab al-Kabir are related to the teachings of moral philosophy, encompassing God as the source of all existence, the universe as a reflection of God's existence and humans as beings possessing freedom and moral responsibility. الملخص يهدف هذا البحث إلى تحديد وتحليل القيم الفلسفية الواردة في كتاب